(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Aim of the study was to analyze the epidemiological features and autopsy findings in different organs of human body due to Aluminum phosphate (ALP) poisoning also known as wheat pills in Lahore. Materials & Methods: Out of 74 suspected poisoning cases, 17 cases (22.97%) were diagnosed as a case of ALP poisoning on the basis of chemical reports during a 3 year study period from January 2006 to December 2008 in the department of Forensic Medicine &Toxicology at K.E.M.U. Lahore. Results: Suspected poisoning cases which were subjected to medico legal autopsies in the department of Forensic Medicine K.E.M.U. Lahore, constituted 2.48% of total autopsies conducted during this study period. ALP poisoning cases accounted for 22.97% of all suspected poisoning cases. It was most common in females (70.58%) than males with M.F ratio 0.41:1 in 3rd decade of life (41.66). Its incidence was highest during the 3rd quarter of the year (41.17%). Suicidal number was highest (100%) in females as compared to males (80%). Accidental cases 20% were seen in males and no homicidal case was reported in either sex.It was more common in rural inhabitants 59% which constituted the 18% population of Lahore. Autopsy findings showed classical signs & symptoms of garlicky pungent odor (47.06%), blood tinged froth (64.7%), cyanosis of face (41.17%) & congestion of brain, liver, spleen, kidneys, lungs & heart in varying degree. Summary: Easy availability & cheapness of ALP tablets is a major factor in the causation of its widespread use among the young females as a tool in the attempted suicide. Recommendations: Public awareness through media regarding its toxicity and lethality is a need of the time. Treatment measures should be made available readily in the hospitals. There should be legal ban on its storage & sale which should be limited to only authorized persons for its usage, storage & sale.